Roles and regulation of myosin V interaction with cargo - Wong, Sara (Adv Biol Regul, 2021)
A major question in cell biology is, how are organelles and large macromolecular complexes transported within a cell? Myosin V molecular motors play critical roles in the distribution of organelles, vesicles, and mRNA. Mis-localization of organelles that depend on myosin V motors underlie diseases in the skin, gut, and brain. Thus, the delivery of organelles to their proper destination is important for animal physiology and cellular function. Cargoes attach to myosin V motors via cargo specific adaptor proteins, which transiently bridge motors to their cargoes. Regulation of these adaptor proteins play key roles in the regulation of cargo transport. Emerging studies reveal that cargo adaptors play additional essential roles in the activation of myosin V, and the regulation of actin filaments. Here, we review how motor-adaptor interactions are controlled to regulate the proper loading and unloading of cargoes, as well as roles of adaptor proteins in the regulation of myosin V activity and the dynamics of actin filaments.